2013
DOI: 10.1128/jcm.00841-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Bruker Biotyper and Vitek MS Matrix-Assisted Laser Desorption Ionization–Time Of Flight (MALDI-TOF) Mass Spectrometry Systems for Identification of Yeasts of Medical Importance

Abstract: We report the first comparative evaluation between the Bruker Biotyper MS (BMS) and the Vitek MS (VMS) for the identification of yeasts. The rate of correct identifications at the species level was comparable using the commercial databases (89.8% versus 84.3%; P ‫؍‬ 0.712), but higher for BMS using an in-house-extended database (100% versus 84.3%; P ‫؍‬ 0.245). Importantly, the rate of misidentification was significantly higher for VMS (1% versus 12.1%; P < 0.0001), including the rate of major errors (0% versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 23 publications
5
58
0
4
Order By: Relevance
“…In our study, the species-level identification rates for Candida species for the two MS systems were comparable to those in recent studies (25,27). However, the identification rate for non-Candida yeasts was lower than that in another study performed in Europe (27).…”
Section: Phenotypic and Molecular Methods Versus Maldi-tof Mssupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, the species-level identification rates for Candida species for the two MS systems were comparable to those in recent studies (25,27). However, the identification rate for non-Candida yeasts was lower than that in another study performed in Europe (27).…”
Section: Phenotypic and Molecular Methods Versus Maldi-tof Mssupporting
confidence: 84%
“…However, the identification rate for non-Candida yeasts was lower than that in another study performed in Europe (27). This may be due to the differences in the protein extraction steps used in the two studies, and further investigations should be focused on the proper extraction method needed for non-Candida yeasts.…”
Section: Phenotypic and Molecular Methods Versus Maldi-tof Msmentioning
confidence: 59%
See 1 more Smart Citation
“…Rosenvinge et al showed that the Biotyper system identified 88% of 200 yeast isolates to the species level using on-plate formic acid testing and a species cutoff of Ն1.700 (40 ). Mancini et al compared the Biotyper system (library v3.0) with protein extraction and Vitek MS (v1.2.0) with on-plate formic acid testing for the identification of 197 yeast isolates (41 ). The rate of correct identifications at the species level was comparable using the commercial databases (90% vs 84%) and improved to 100% using the Biotyper system with an in-housedeveloped database.…”
Section: Performance Of Maldi-tof Ms For Identification Of Fungimentioning
confidence: 99%
“…Son dönemlerde MALDI-TOF MS, rutin mikrobiyoloji laboratuvarında mikroorganizmaların tanımlanmasında güvenilir sonuç vermesi, hızlı ve kolay uygulanması ve maliyetinin düşük olması nedeniyle umut veren bir sistem olarak ortaya çıkmıştır (7) .…”
Section: Discussionunclassified